Cabaran Mahasiswa Akademi Pengajian Islam, Universiti Malaya (APIUM) Dalam Isu Kesihatan Mental: Challenges of Academy of Islamic Studies Students, University of Malaya (AISUM) in Mental Health Issues - Sapuan, Ainul Natasya; Ali @ Mat Zin, Aizan (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2023)
This article aims to evaluate challenges of Academy of Islamic Studies students, University of Malaya in mental health issues. A good mental health is of paramount importance for every individual, and mental health issue among university students especially, is getting worse. A previous study shows that one out of four students at Higher educational institutions had mental health issues such as depression, anxiety, and stress. This study was carried out by using mix mode approaches i.e. qualitative and quantitative. Data collection use two methods i.e documentation and quetionnaires. Quetionnaires were distrubuted to 111 respondents of the AISUM. Random stratified sampling determined certain criteria including undergraduate students, both man and woman, year of study, and type of programs. All collected data were analysed by using statistical analysis i.e Statistical Package for the Social Sciences (SPSS) version 27. Finding exhibits that students of the Academy of Islamic Studies have good mental health level due to religious-spiritual coping style although they had challenges in learning process that affected their mental health . The highest mean scores shows that learning aspect is the most stressful factor throughout their student life in campus followed by personal problems. In conclusion, by choosing religion as a way of life, it helps students in coping with mental health issues.